Evaluación del macerado de chocho (Lupinus mutabilis Sweet) para control de gusano cogollero (Spondoptera frugiperda) en el cultivo de maíz (Zea mays L.) en la localidad Plaza Arenas-Latacunga 2022. - Chiquin Lema, Angie Raquel (2022)
The research was conducted with the objective of evaluating the chocho macerate for the control of codling moth (Spondoptera frugiperda) in corn (Zea mays L.) at different doses and frequencies to reduce the use of chemical insecticides. The corn seed was obtained from the seed bank of the Technical University of Cotopaxi, which was UTC0020. A completely randomized block design (DBCA) of 2x2x2+1 control and three replications was implemented, giving a total of twenty-seven experimental units from which 10 plants per treatment were selected for the study, this being the net plot. The factors under study were maceration sources (Factor A), dose (Factor B), frequencies (Factor C). The statistical analyses of the data were carried out using the Infostat program from which the analysis of variance (ADEVA) was obtained and a 5% Tukey test was performed. It could be evidenced that the alkaloids are growth inhibitors for the variable height of the silver (m), so that a considerably homogeneous height could be obtained. The results of the variable incidence of budworm in the plant (%) were as follows: the T5 treatment (Chocho tender with a dose of 150 gr and a frequency of 15 days) was the one that helped the most to control the budworm, with 53.33% at 110 days and 10% at 170 days. Treatment T4 (dry chocho with a dose of 75 g and a frequency of 30 days) was the one with the highest incidence of budworm with 76.67% at 110 days and 50% at 170 days. The maceration source of tender chocho was the most effective for budworm control.